T2‐Weighted intracranial vessel wall imaging at 7 Tesla using a DANTE‐prepared variable flip angle turbo spin echo readout (DANTE‐SPACE). Issue 2 (18th February 2016) - Viessmann, Olivia; Li, Linqing; Benjamin, Philip; Jezzard, Peter
Abstract : Purpose: To optimize intracranial vessel wall imaging (VWI) at 7T for sharp wall depiction and high boundary contrast. Methods: A variable flip angle turbo spin echo scheme (SPACE) was optimized for VWI. SPACE provides black‐blood contrast, but has less crushing effect on cerebrospinal fluid (CSF). However, a delay alternating with nutation for tailored excitation (DANTE) preparation suppresses the signal from slowly moving spins of a few mm per second. Therefore, we optimized a DANTE‐preparation module for 7T. Signal‐to‐noise ratio (SNR), contrast‐to‐noise ratio (CNR), and signal ratio for vessel wall, CSF, and lumen were calculated for SPACE and DANTE‐SPACE in 11 volunteers at the middle cerebral artery (MCA). An exemplar MCA stenosis patient was scanned with DANTE‐SPACE. Results: The 7T‐optimized SPACE sequence improved the vessel wall point‐spread function by 17%. The CNR between the wall and CSF was doubled (12.2 versus 5.6) for the DANTE‐SPACE scans compared with the unprepared SPACE. This increase was significant in the right hemisphere ( P = 0.016), but not in the left ( P = 0.090). The CNR between wall and lumen was halved, but remained at a high value (24.9 versus 56.5). Conclusion: The optimized SPACE sequence improves VWI at 7T. Additional DANTE preparation increases the contrast between the wall and CSF. Increased outer boundary contrast comes at the cost of reduced inner boundary contrast. Magn Reson Med 77:655–663, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.